Variability in DPA and Calcium Content in the Spores of Clostridium Species - Jamroskovic, Jan; Chromikova, Zuzana; List, Cornelia; Bartova, Barbora; Barak, Imrich; Bernier-Latmani, Rizlan (Frontiers in Microbiology, 2016)
Spores of a number of clostridial species, and their resistance to thermal treatment is a major concern for the food industry. Spore resistance to wet heat is related to the level of spore hydration, which is inversely correlated with the content of calcium and dipicolinic acid (DPA) in the spore core. It is widely believed that the accumulation of DPA and calcium in the spore core is a fundamental component of the sporulation process for all endospore forming species. We have noticed heterogeneity in the heat resistance capacity and overall DPA/calcium content among the spores of several species belonging to Clostridium sensu stricto group: two C. acetobutylicum strains (DSM 792 and 1731), two C. beijerinckii strains (DSM 791 and NCIMB 8052), and a C. collagenovorans strain (DSM 3089). A C. beijerinckii strain (DSM 791) and a C. acetobutylicum strain (DSM 792) display low Ca and DPA levels. In addition, these two species, with the lowest average Ca/DPA content amongst the strains considered, also exhibit minimal heat resistance. There appears to be no correlation between the Ca/DPA content and the phylogenetic distribution of the C. acetobutylicum and C. beijerinckii species based either on the 16S rRNA or the spoVA gene. This finding suggests that a subset of Clostridium sensu stricto species produce spores with low resistance to wet heat. Additionally, analysis of individual spores using STEM-EDS and STXM revealed that DPA and calcium levels can also vary amongst individual spores in a single spore population.